Design and Performance Improvement of Pico Hydro Turbine - Mohd Badzli Shah, Mohamad Hafidz (IRC, 2018)
One of the effective way to encourage the electricity generation using water as the main source is by introducing Pico hydro generation system. Water flow from the river upstream has kinetic energy and potential energy to rotate the turbine that connected towards the generator to produce electricity. Pico hydro system is a clean energy as it produces electricity by just having water flow instead of fuel which is expensive and causes pollution. Furthermore, this research is focusing on the development of Pico hydro generation system to produce low capacity energy for Royal Belum rural community. This system can support low capacity equipment such as motor and bulb that will be used in their daily life. Besides, the purpose of this project is to study on the improvement towards the turbine design, configuration and performance of previous design of Pico hydro that have been fabricated by the previous final year student of Universiti Teknologi PETRONAS (UTP) with power coefficient of 0.12. The author proposed new duct wall design with several number of Savonius turbine blades to be simulated by ANSYS Fluid Fluent software to study the performance of each turbine. The simulation conducted for only 5m/s of water velocity at the inlet with 10mm sliced geometry due to limited number of element for ANSYS Academic Version with assumption of 1m head for the power output calculation. The result shows that sixteen blades Savonius turbine is the best as two, four and eight blades turbine will lead the turbine to stall due to the huge turbulent of whirlpool developed between the turbine blades. The power coefficient for this design is 0.21 which is higher than the previous model. Proper configuration of Pico hydro will lead to higher power output generated.